2014
DOI: 10.1002/14651858.cd006990.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions for chronic rhinosinusitis with nasal polyps

Abstract: We are unable to reach any conclusions as to whether isolated nasal polypectomy or more extensive sinus surgery is a superior surgical treatment modality for chronic rhinosinusitis with nasal polyps. There is a need for high-quality randomised controlled trials to assess whether additional sinus surgery confers any benefit when compared to nasal polypectomy performed in isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 55 publications
0
46
0
8
Order By: Relevance
“…1125 Although ESS has become the mainstay for achieving these aims, it is notable that strong evidence for the superiority of ESS over simple polypectomy is lacking. 7,1126 Moreover, for CRSwNP specifically (as opposed to CRS overall), there is a similar lack of high-level evidence for the superiority of surgery over medical therapy for nasal polyposis. 1127 To be clear, evidence can be extrapolated from some studies, especially lower levels of evidence, to support the superiority of surgery in CRSwNP.…”
Section: Ixe Aecrs: Complicationsmentioning
confidence: 99%
“…1125 Although ESS has become the mainstay for achieving these aims, it is notable that strong evidence for the superiority of ESS over simple polypectomy is lacking. 7,1126 Moreover, for CRSwNP specifically (as opposed to CRS overall), there is a similar lack of high-level evidence for the superiority of surgery over medical therapy for nasal polyposis. 1127 To be clear, evidence can be extrapolated from some studies, especially lower levels of evidence, to support the superiority of surgery in CRSwNP.…”
Section: Ixe Aecrs: Complicationsmentioning
confidence: 99%
“…Chronic rhinosinusitis with nasal polyposis (CRSwNP) is one of the two major phenotypes of chronic rhinosinusitis (CRS) and is defined by the presence of nasal polyps in the middle meatus . Studies have shown that CRSwNP negatively affects quality of life and is a common problem worldwide, with prevalence estimates of 0.2%‐4% . While surgery provides significant benefit in symptomatology and respiratory health, as many as 40% of the patients with CRSwNP may develop recurrent polyposis within 12 months postoperatively .…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies have shown that CRSwNP negatively affects quality of life and is a common problem worldwide, with prevalence estimates of 0.2%-4%. 2,3 While surgery provides significant benefit in symptomatology and respiratory health, 4,5 as many as 40% of the patients with CRSwNP may develop recurrent polyposis within 12 months postoperatively. 6,7 Clinical factors such as asthma prevalence, as well as aspirinexacerbated respiratory disease (AERD), appear to be associated with higher recurrence rates of nasal polyps.…”
mentioning
confidence: 99%
“…In a recently published Cochrane review considering the effectiveness of different surgical interventions for CRSwNP, Sharma et al [35] evaluated trials where patients were randomised to different surgical procedures. After an initial search identified 3014 records, only 6 met the criteria above, and these were all excluded due to risk of bias and other limitations.…”
Section: Nasal Polypectomy Alone Versus Adjunctive Endoscopic Sinus Smentioning
confidence: 99%